Effect of a 12-km march with military load and MAG machine gun on orthostatic postural balance (Research, Society and Development, 2026)
The progressive increase in the load carried by military personnel, resulting from the modernization of combat equipment, has intensified the physiological and biomechanical demands during operational marches, potentially compromising postural control. The main objective was to analyze the effect of a 12-km march while carrying military load and a MAG machine gun on orthostatic postural balance. The present study is characterized as a quasi-experimental research with a within-subject design, involving 15 male military personnel. Postural control was assessed using a stabilometric test on a force platform, before and after the 12-km march. The analyzed variables included center of pressure (COP) area, mean mediolateral velocity, and mean anteroposterior velocity. The results demonstrated a statistically significant increase in COP area and mean mediolateral velocity after the march, indicating greater postural sway, whereas mean anteroposterior velocity did not show a significant difference. It is concluded that the 12-km operational march performed while carrying military equipment and a MAG machine gun imposes a relevant overload on the postural control system, evidencing functional impact resulting from prolonged effort associated with load carriage.